ANALISIS PENGARUH UTILITARIAN SHOPPING VALUE DAN HEDONIC SHOPPING VALUE TERHADAP INTENT TO ONLINE REPURCHASE DENGAN PERAN PERCEIVED VALUE SEBAGAI MEDIATOR - Andani, Nugraha Fitra; Soesanto, Harry (Diponegoro Journal of Management, 2015)
This study aimed to analyze the influence of internet shopping value is utilitarian shopping value and hedonic shopping value to intent to online repurchase with using perceived value as mediator variable study case on product fashion consumer of Faculty of Econimics and Business, Diponegoro University. Utilitarian shopping value based on critical thinking. Hedonic shopping value based pleasure. Perceived value is difference between the benefits received by consumer with all costs or a particular offer. Intent to online repurchase is an interest in re-purchase showing the desire to online re-purchase.            This study used non-probability sampling is used for judgmental sampling. Data were collected from 115 respondents selected using criteria that should have made a online purchase of fashion products at least twice. The method analysis used in this research was Maximum Likelihood test using the program of AMOS version 20.0.            The results show that the utilitarian shopping value and hedonic shopping value has positive influence on perceived value but did not positive influence on intent to online repurchase. Then, perceived value has positive influence on intent to online repurchase on product fashion consumer of Faculty of Econimics and Business, Diponegoro University.